EKSISTENSI PEMBERLAKUAN SISTEM E-COURT DALAM PERADILAN TATA USAHA NEGARA DI INDONESIA - Krisyulaeni (Yustitia, 2021)
The massive rate of technological development that is happening in Indonesia today, has led various judicial bodies in all parts of the world, including Indonesia to then begin to adopt and take advantage of these technological developments. The procurement of e-court itself began to be implemented after the Supreme Court Regulation Number 3 of 2018. PTUN which stands for the term State Administrative Court is one of the judicial institutions in Indonesia whose position is under the Supreme Court. The Supreme Court itself has made various efforts through convenience in terms of administrative services through a system called the electronic court or hereinafter referred to as e-court, and then by law, this is contained in Supreme Court Regulation Number 1 of 2019. Keywords : Technological developments, Electronic courts, State Administrative Courts